Technology Based Village (Case Study of Engineering Students at Mpu Tantular University KKN 2022) Sukasari Village/Subdistrict, Rumpin District, Bogor District/City, West Java Province - Edison Hotaguan Manurung; Hansen Louister; Alif Prajoko; Agus Purba; Ary Rafindo Sianturi; Cladino T M Ngabut; Fatur Rizki Hidayat; Michael Oloan Silaen; Shaumi Hayati Radinda; William Y P Simanjuntak (Indonesian Journal of Advanced Social Works, 2022)
The classroom building has an important role in the growth and development of early childhood. For this reason, it is very important to ensure that children are within the scope of the classroom as they should be. The state of technology that is developing rapidly should be able to educate educators in PAUD about how children's classrooms should be used. Based on the results of observations on PAUD in Sukasari Village, Kab. Bogor West Java found classrooms that were quite unsupportive. For this reason, a Community Service Program (KKN) was designed to be carried out by students of the Faculty of Engineering, University of Mpu Tantular through community service methods such as rejuvenating the building at PAUD Al-Husaeni to create safe, comfortable, and attractive classrooms for children studying at there.